2013
DOI: 10.1002/zaac.201300104
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of η6‐Arene Ruthenium Complexes Bearing Oxopentadienyl and Phosphine Ligands

Abstract: An addition reaction of dinuclear [(η6‐C6Me6)Ru(η3, 1‐exo‐syn‐CH2CHCHCHO)]2(BF4)2 (1) with different Lewis bases in acetone results in the formation of mononuclear [(η6‐C6Me6)Ru(η3‐exo‐syn‐CH2CHCHCHO)(L)](BF4) (L = PMe3, 2; PPh3, 3; PHPh2, 4; Ph2PEtPy, 6; CO, 7) and dinuclear [{(η6‐C6Me6)Ru(η3‐exo‐syn‐CH2CHCHCHO)}2(μ2‐dppe)](BF4)2 (5). The addition of Ph2PCH2CH2PPh2 to the dinuclear product 1 affords 5 which show a bridging phosphine between two ruthenium centers. A comparative study of the new cationic arene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Nevertheless, there are several scattered reports of phenyl-substituted pentadienyl transition-metal complexes, but the only systematic study, focusing on open and half-open ruthenocenes with phenyl substitutents, was reported by Ernst . Furthermore, several complexes with “edge-bridged” pentadienyl ligands such as cyclooctadienyl and heteropentadienyl derivatives have been investigated . From these studies several distinct features of the pentadienyl ligand have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are several scattered reports of phenyl-substituted pentadienyl transition-metal complexes, but the only systematic study, focusing on open and half-open ruthenocenes with phenyl substitutents, was reported by Ernst . Furthermore, several complexes with “edge-bridged” pentadienyl ligands such as cyclooctadienyl and heteropentadienyl derivatives have been investigated . From these studies several distinct features of the pentadienyl ligand have emerged.…”
Section: Introductionmentioning
confidence: 99%